2018
DOI: 10.1249/mss.0000000000001597
|View full text |Cite
|
Sign up to set email alerts
|

Dehydration Impairs Cycling Performance, Independently of Thirst: A Blinded Study

Abstract: These data indicated that hypohydration decreased cycling performance and impaired thermoregulation independently of thirst, while the subjects were unaware of their hydration status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
51
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(64 citation statements)
references
References 27 publications
1
51
1
3
Order By: Relevance
“…To address this issue, more recent research has blinded subjects from their hydration status (2,12,28,50). These studies have used two different methods to manipulate hydration status; 1) intravenous delivery of isotonic fluids (12,50) and 2) intragastric delivery of water via a gastric feeding tube (2,28). Interestingly, the different methods appear to induce divergent physiological and performance responses.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To address this issue, more recent research has blinded subjects from their hydration status (2,12,28,50). These studies have used two different methods to manipulate hydration status; 1) intravenous delivery of isotonic fluids (12,50) and 2) intragastric delivery of water via a gastric feeding tube (2,28). Interestingly, the different methods appear to induce divergent physiological and performance responses.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the different methods appear to induce divergent physiological and performance responses. Studies using intragastric rehydration with water, combined with standardised oral rehydration, report blinded hypohydration to impair performance (2,28), whilst those using intravenous rehydration with isotonic saline do not (12,50). Importantly, manipulating hydration status via intravenous rehydration with isotonic saline meant serum osmolality (12,50) and thirst sensation (50) remained elevated at levels equivalent to hypohydration, irrespective of hydration status.…”
Section: Introductionmentioning
confidence: 99%
“…16,17 In contrast, few investigations have observed performance differences even when thirst was matched by mouth rinsing or water ingestion. 3,15,18 In the present study, subjects during the HYP had lower power output and cycling speed in the second time trial, even when hypohydration was just 1% of bodyweight. However, thirst was not higher during the first two exercise bouts, since subjects were drinking 25 mL of water every 5 minutes and 1 km of the steady-state and time trial, respectively.…”
Section: Discussionmentioning
confidence: 42%
“…The present study is not without limitations. Regarding the methodology of blinding, the intravenous fluid induced plasma volume expansion in the EUH trial that we would probably not see if the subjects were receiving the same fluid volume orally (Table 1) as shown in a previous study by the same authors 15 and elsewhere. 26 The authors found that infusion of 0.9% NaCl as a blinding method expanded PV (~3%) and found differences in performance compared to HYP trial under a mild degree of dehydration.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation